Self-Reported Health and Happiness Among Sub-Regions of Asia: The World Value Survey 2017-2021 (Journal of Asian Development Studies, 2024)
This paper compared the differences in self-assessed health and happiness among five Sub-regions of Asia, namely, South Asia, Central Asia, West Asia, Eastern Asia, and South East Asia. The ng data was collected from the World Value Survey between 2017 and 2021 (Wave-Seven). A total of 3,278 participants from five sub-regions were surveyed. Self-Rated Health (SRH) and happiness were measured using a self-reported questionnaire. The results showed that the SRH and happiness levels were significantly high, with 81.09% expressing satisfaction. Gender-wise, females display reduced odds of happiness compared to males (OR=0.73, [SE/Z] =-0.07/-3.15), indicating a gender-based disparity. Higher education, financial satisfaction, and income levels are significantly associated with improved health perceptions. Higher satisfaction with the financial situation and income scales also demonstrates significant associations with happiness. As individuals age, there is a substantial increase in the odds of reporting good health, with the highest odds observed in the 65+ age group.